The Absolute Spectator - Carroggio, Alberto (Advances in Social Sciences Research Journal, 2018)
The painter, as an absolute spectator, reaches the limit of the observable. When analyzing the process of pictorial representation, he realizes that he is observing his own product, because when he decomposes the surface into its components, he discovers the color and beyond color there is nothing. It is necessary to reverse the process of analysis and to undertake the synthesis process: that is, to generate concepts that support actions that, ultimately, are based on personal attitudes, among which confidence in oneself is the culmination of the process and, nevertheless, determines the action from the beginning. From this perspective, the definition of representation is a whole in which the notions used by the mind intervene to elaborate the image of the environment and, consequently, the components of the definition of representation are of a subjective nature.